The role of organizational learning climate and individual's learning goal orientation in training and development activity participation of R&D organization employees: Informal vs. formal training and development activities - Lee, Sunhee (Korean Journal of Industrial and Organizational Psychology, 2013)
The study examined the relationships between organizational learning climate and individual's learning goal orientation and employee's participation in training and development activities and whether the relationships differ between informal versus formal training and development activities. Multi-level analyses on survey data from a total of 1,087 employees of 11 R&D organizations showed that learning climate and learning goal orientation were positively related to participation in training and development activities even after organizational training budget was controlled for. Further, organizational learning climate was more closely related to formal training and development activities while individual's learning goal orientation was more closely related to informal training and development activities. The theoretical and practical implications as well as directions for future research were discussed.